Kant and global distributive justice - Loriaux, Sylvie 1972- (Cambridge elements, 2020)
This Element argues that although Kant's political thought does not tackle issues of global poverty and inequality head on, it nonetheless offers important conceptual and normative resources to think of our global socioeconomic duties. It delves into the Kantian duty to enter a rightful condition beyond the state and shows that a proper understanding of this duty not only leads us to acknowledge a duty of right to assist states that are unable to fulfil the core functions of a state, but also provides valuable hints at what just transnational trade relations and a just regulation of immigration should look like